The Effect of Educational Intervention on Selection of Delivery Method Based on Health Belief Model. - Mohammad Hossein Baghianimoghadam; Tahere Hashemifard; Samira Jafari; Parvin Yadolahi; Malihe Kamali moradzadah; Faeze Hashemifard (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction- Pregnancy is a natural process that can lead to fatal accidents and serious injuries to the mother and fetus. When there is no possibility of vaginal delivery for the mother and There is a possible risk to the mother and children, Cesarean delivery is performed. In many cases there is no medical necessity for a cesarean delivery But ignorance, beliefs, behaviors and attitudes of non-false test has been determiner the method of delivery . Materials and methods-This was an experimental study that was done on pregnant women who were referee to health centers of Yazd city .The samples were 130 first pregnant mothers that were divided in two groups(65 case group and 65 control group). The samples were selected by random sampling. The data was collected by a researcher making questionnaire include 4 section. At first ,two groups completed the questionnaires , then the intervention was conducted for case group based on the Health Belief Model in given 45-minute sessions. about 2month after intervention , two groups completed the questionnaires twice. The data was analyzed with SPSS18 and describing Parameters the mean and the standard deviation . The relationship between structural and demographic variables were analyzed using Mann-Whitney, Kruskal-Wallis and Chi-square were analyzed. Results- In this study, the mean age of women was 24.36 ± 3.73 and the mean gestational age 31.53 ± 2.35, respectively.The results showed that there was significant difference between case and control groups after intervention in Perceived susceptibility(p=0.001),perceived threat(p=0.001),perceived benefit(p=0.01), perceived barrier(p=0.01) and knowledge(p=0.001).There was no significant difference between self efficacy (p=0.069)and methods of delivery between two group after intervention. Discussion- In this study educational intervention based on health belief model increased the awareness of pregnant women, However ,it has not been effective on their performance. Because many factors other than knowledge are involved in the choice of delivery method, It is proposed to enhance the efficiency of this model simultaneously different patterns that can be used effectively on other factors.